Development of Booklet on Phytoremediation of Tapioca Wastewater Using Aquatic Plants as a Learning Resource for Environmental Change - Nuraini, Firli; Herlina, Lina (Universitas Negeri Semarang, 2025)
This study developed a learning resource booklet on phytoremediation of tapioca wastewater using aquatic plant. The development research employed the Research and Development (R&D) method using the ADDIE model. Conducted at Laboratory of the Biology Department UNNES and SMA Negeri 1 Sigaluh,. The research aimed to create a valid, practical, and effective learning tool. Two validators assessed the booklet's validity, while teachers and students evaluated its practicality via questionnaires. Student learning outcomes, measured through pre- and post-tests, determined effectiveness. The booklet demonstrated high validity, achieving 92,86% for content and 90% for media. Practicality was also high, with teachers rating it 81,25% and students 89,69%. Critically, the booklet significantly improved student learning outcomes. Average pre-test scores of 32,09 rose to 79,55 on the post-test, with 80% of students achieving mastery, exceeding the school's minimum classical completeness criteria. These results confirm the booklet's effectiveness in enhancing student understanding of environmental change, specifically phytoremediation. The conclusion of this research is that the booklet on phytoremediation of tapioca industry liquid waste using aquatic plants is highly valid, practical, and effective as a learning resource for the material on environmental change.